Prousts blik. Synets dobbelthed i På sporet af den tabte tid - Povlsen, Steen Klitgård (Passage - Tidsskrift for litteratur og kritik, 2015)
Steen Klitgård Povlsen: “Proust’s Look: The Duality of Looking in In Search of Lost Time” Marcel Proust was part of that “denigration of the vision” as the dominating sense that according to Martin Jay can be observed in European culture around 1900. In In Search of Lost Time there can be found a radical criticism of the capacity of the look to maintain the true concept of the world. But also an account of art’s possibility to compensate for this failure. The article describes this split between blindness and insight which is a main theme in Proust’s work.